Quand Aznavour va chanter Les disparus… - Janine Altounian (Amnis)
Which transmission carry in them the Armenians of the diaspora who accompany the President of the French Republic for a State visit in Armenia? The paper starts by questioning the particular acuity of what these heirs to the survivors of the Armenian genocide of 1915 feel when, 91 years later, the last witnesses leave them. Then, the two parts of the article evoke first, at the individual psychic level, the impossible words that their descendants were in charge of carrying, and secondly, at the politico-social level, the necessity in which they are to move and hybridize their inheritance to make it speakable and to pass it on.